(untitled) (Bangladesh Journal of Microbiology, 2010)
Microbial biomass carbon (C) and nitrogen (N) and their contribution to soil organic carbon and total N contents were assessed in soils collected from Bilashchara Tea Estate under Bangladesh Tea Research Institute (BTRI), Srimangal of Moulavibazar district, and Sripur Tea Garden under Jaintapur of Sylhet district. Microbial biomass C and N in Bila shchara Tea Estate soils varied from 90.4-144.0 and 20.5-29.0 mg/kg soil, and that of Sripur Tea Garden soils varied from 120.7-362.0 and 26.6-59.5 mg/kg soil, respectively. Within the two tea growing areas biomass C/N ratios ranged from 3.35-6.12. Relationships between biomass C and organic carbon and biomass N and total N were positively correlated. The contribution of biomass C to soil organic C was 1.23%, ranging from 0.9-1.55% and the contribution of biomass N to total N content of the soils ranged from 1.19-2.89%. Keywords: Biomass carbon (C); Biomass nitrogen (N); Organic C; Total N; Tea soil DOI: http://dx.doi.org/10.3329/bjm.v25i1.4850 Bangladesh J Microbiol, Volume 25, Number 1, June 2008, pp 21-25